Hubungan usia dengan tingkat dispareuni pada masa klimakterium di Dusun Jambidan Banguntapan Bantul Yogyakarta 2013 - Retna Heliansari Astuti; Dyah Noviawati Setya Arum; Margono Margono (Jurnal Kesehatan Ibu dan Anak, 2013)
Success of health building can influence increasing live age expectation from 66,7 years old for women and 62,9 years old for men at 1995 become 71 years old for women and 67 years old for men at 2005. At 2O2O projected that total inhabitant at age more than 60 will be 28,8 million or 11 ,34% of Indonesian’s people. By advance of population from late age need to increase priority and quality live. Sexuality is one of determinant from quality live of late age. Former study that sexual behavioral and sexual disfunction also effort to find help for people at range 40-80 years old can be held in several country in Asia include Indonesia, reported from 6700 people 82% men and 64% are women at late age said had intercourse in the last 1 year From interview, 20 to 30% they complain that had sexual dysfunctional such as early ejaculation, erectile disorder perturbation, and for women especially like uninterest to had intercourse, difficulty in lubrication, and difficulty to had orgasm. The Objection is to identify correlation of age and dyspareunia level al climatarian age in Jambidan Village Banguntapan Bantul Yogyakarta 2013. This study used an analytic observational with cross sectional design. Technique sampling used random sampling; instrument of study is questioner using primer data. Data analysis by univariate and bivariate use Kendall-tau. Result: the most women at climatarian age who had dyspareunia 59,8% are average dyspareunia. Kendall tau result are p-value 0,00 < 0,05 which means there are significant correlation of age with dyspareunia level at climatarian age. Analysis use bivariate can take a conclusion that pain intensity more influence to dyspareunia level with result 0.21899 > 0.18139. Conclusion: there are correlation of age and dyspareunia level with climatarian period. Coming to late age have more risk to have hard dyspareunia.